INTEGRATING EDUCATIONAL VALUES OF THE MINANGKABAU MATRILINEAL SYSTEM INTO THE SOCIAL SCIENCE EDUCATION CURRICULUM - Fajri, Suryadi; Asnimawati, Asnimawati; Febrianti, Sari Febrianti; Ulaini, Nisa; Putri, Aulia Rahmi (UIN Sumatera Utara, 2025)
This study explores the educational values embedded in the Minangkabau matrilineal kinship system and evaluates their relevance to the development of the Social Science education curriculum in Indonesia. It advocates for the integration of local wisdom as a foundational source for contextualizing Social Science instruction. Employing a qualitative descriptive approach and thematic analysis, data were gathered through in-depth interviews, participatory observations, and document analysis across various Minangkabau communities. The findings reveal key values inherent in the matrilineal tradition—such as justice, responsibility, collective deliberation, trust, mutual cooperation, and the pivotal role of women as primary educators within the family. These values offer rich pedagogical insights and cultural frameworks that support the design of culturally responsive and socially grounded learning experiences. The study argues that embedding these local values within the Social Science curriculum can foster a more inclusive, relevant, and character-oriented education aligned with the principles of national identity and local heritage.Keywords: Education, Matrilineal Kinship, Minangkabau, Social Science Curriculum, Local Wisdom Integration